Comparison of Malaysian and Indonesian Vocabulary in Upin and Ipin Cartoon Animated Films on the National TV Channel - Mutia Febriyana; Shella Dwinta (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Kata Kunci ; Perbandingan Kosa Kata, Malaysia dan Indonesia, Film Kartun Upin dan Ipin Abstract: Language is a tool for communicating or conveying something that comes to mind, which means conveying thoughts, ideas, concepts, or feelings. The language in the Upin and Ipin Cartoon Animation film aims to increase knowledge by emphasizing the language vocabulary contained in the Upin and Ipin Cartoon Animation film seen from the synonymy and homonymy vocabulary of Malaysian Malay and Indonesian. This research method uses descriptive method with qualitative data analysis. The data analysis techniques used were viewing, listening, recording, and taking notes (the language vocabulary contained in the Upin and Ipin Cartoon Animation film), analyzing the existing data, then drawing conclusions from a comparison of the Malay Malay and Indonesian vocabulary. The results of this study state that there are synonyms and homonyms for Malaysian Malay and Indonesian Indonesian vocabularies which are expressed in the animated cartoons Upin and Ipin on the National TV Channel. The scenario shown is about love, knowledge, and friendship. Keywords ; Comparison of Vocabulary, Malaysia and Indonesia, Upin and Ipin Cartoon Films